A method for improving the oxidation resistance of metal bonding layer of thermal barrier coating

By performing pulse laser remelting treatment on the surface of the nickel-based or cobalt-based metal bonding layer of the thermal barrier coating, the weak bonding problem between the splash particles and the bonding layer substrate is solved, and a uniform α-Al2O3 oxide film is formed, which significantly improves the oxidation resistance and service life of the thermal barrier coating.

CN115627438BActive Publication Date: 2025-03-14XI AN JIAOTONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211350147.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-31
Publication Date
2025-03-14
Estimated Expiration
2042-10-31

AI Technical Summary

Technical Problem

During the high-temperature service, the existing thermal barrier coating metal bonding layer has weak bonding between the splash particles and the bonding layer substrate, resulting in unevenness and rapid growth of the oxide film, thereby shortening the service life of the thermal barrier coating.

Method used

A nickel-based or cobalt-based metal bonding layer was prepared on the surface of the nickel-based high-temperature alloy matrix by thermal spraying, and the splash particles on the surface of the remelting bonding layer were treated by pulsed laser scanning to eliminate weak bonding, and finally a ceramic thermal insulation layer was prepared on the surface.

Benefits of technology

The antioxidant performance of the bonding layer surface is significantly improved through laser treatment, forming a single and uniform α-Al2O3 oxide film, extending the service life of the thermal barrier coating, and reducing cost and operational complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115627438B_ABST
    Figure CN115627438B_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the oxidation resistance of a metal bonding layer of a thermal barrier coating. The method comprises the following steps: firstly, preparing a bonding layer on the surface of a high-temperature alloy substrate, then treating the bonding layer with a pulsed laser so that splashing particles on the bonding layer surface can be remelted, thereby solving the problem of poor contact between the splashing particles and the bonding layer substrate; finally, preparing a ceramic thermal insulation layer on the bonding layer surface, thereby achieving the purpose of forming a single uniform α-Al2O3 on the bonding layer surface during subsequent service, thereby effectively improving the oxidation resistance of the bonding layer and the service life of the thermal barrier coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of metal thermal barrier coatings, and in particular relates to a method for improving the oxidation resistance of a metal bonding layer of a thermal barrier coating. Background Art

[0002] With the continuous development of gas turbine technology, the increasingly high turbine inlet temperature has posed a greater challenge to the heat resistance limit of turbine blade materials. Thermal barrier coating is a thermal insulation coating used on gas turbine turbine blades. It can effectively reduce the surface temperature of turbine blades in combination with the air film cooling technology on the surface of turbine blades. Thermal barrier coatings usually include a metal bonding layer and a ceramic insulation layer, in which the ceramic layer plays a role in heat insulation and the bonding layer plays a role in resisting high-temperature oxidation. In addition, during the high-temperature service of the thermal barrier coating, since the porous ceramic insulation layer cannot block the entry of oxygen, an oxide film will also be generated on the surface of the metal bonding layer, which is called thermally grown oxide (TGO).

[0003] Studies have shown that the growth rate of TGO is an important factor in controlling the service life of thermal barrier coatings for gas turbines. Taking the commonly used bonding layer material MCrAlY as an example, TGO usually comes in two categories: one is dense, slow-growing α-Al2O3; the other is loose, porous, fast-growing mixed oxides. If the service life of gas turbines is to be significantly improved, the composition of TGO needs to be controlled to a single aluminum oxide film, so that the growth rate of TGO can be slowed down, thereby improving the service life of thermal barrier coatings.

[0004] At present, the thermal spraying preparation methods of MCrAlY bonding layer mainly include low-pressure plasma spraying and supersonic flame spraying. The bonding layer surface prepared by these two spraying methods is composed of semi-molten particles, which is of great significance for improving the surface roughness of the bonding layer and enhancing the mechanical locking effect between the bonding layer and the ceramic layer. At the same time, since the thermal spraying method can make the MCrAlY particles melt or semi-melt, when the molten droplets collide with the substrate, splashing will inevitably occur. The splashing particles will be deposited on the surrounding bonding layer surface. Such splashing particles are weakly bonded to the bonding layer substrate, which will lead to the Al element in the splashing particles being consumed first in the subsequent high-temperature service process. The Al element under the splashing particles cannot be transmitted through the weakly bonded interface, so mixed oxides will be generated. The rapidly growing mixed oxides will cause the thermal barrier coating to fail prematurely. Therefore, how to effectively solve the weak bonding problem between the splashing particles and the bonding layer substrate without destroying the overall surface roughness of the bonding layer is a key factor in effectively improving the antioxidant performance of the bonding layer and the service life of the thermal barrier coating.

[0005] In the existing technology, the anti-oxidation performance of the bonding layer is mainly improved by promoting the selective oxidation of the oxide film on the surface of the bonding layer by methods such as the composition ratio of the bonding layer powder material, increasing the Al / Ni ratio, and coating the bonding layer with an Al film. This is costly and complicated to operate. Therefore, there is an urgent need for a method for improving the anti-oxidation performance of the bonding layer that is based on commercial powders, simple to operate, and low in cost. Summary of the invention

[0006] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a method for improving the antioxidant performance of the metal bonding layer of the thermal barrier coating, which can effectively solve the problem of weak bonding between the splashing particles and the bonding layer matrix, thereby effectively improving the antioxidant performance of the bonding layer and the service life of the thermal barrier coating.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] The present invention discloses a method for improving the anti-oxidation performance of a metal bonding layer of a thermal barrier coating, comprising the following steps:

[0009] S1: preparing a nickel-based or cobalt-based metal bonding layer on the surface of a nickel-based high-temperature alloy substrate by thermal spraying;

[0010] S2: Perform laser scanning on the bonding layer surface to remelt the splash particles on the bonding layer surface to eliminate the weak bond between the splash particles and the bonding layer surface;

[0011] S3: preparing a ceramic thermal insulation layer on the surface of the specimen treated in S2.

[0012] Preferably, in S1, the thermal spraying method for preparing the metal bonding layer adopts a low-pressure plasma spraying method or a supersonic flame spraying method.

[0013] Preferably, in S1, the powder component elements of the prepared metal bonding layer include Co, Cr, Ni, Al and Y.

[0014] Preferably, in S1, the thickness of the prepared nickel-based or cobalt-based metal bonding layer is 80-150 μm.

[0015] Preferably, in S2, a pulsed laser is used for laser scanning processing, the power of the laser is between 50W and 200W, the peak power is greater than 10kW, and the pulse width is less than 10μs.

[0016] Further preferably, the horizontal angle between the laser and the sample is set to 45° to 60°.

[0017] Preferably, in S2, the laser frequency is 100-200K, the scanning speed is 5-15 mm / s, and the laser scans three times, with the normal direction of the sample surface as the axis, and rotates 120° along the axis each time.

[0018] Preferably, in S2, argon atmosphere protection is performed during the laser scanning process.

[0019] Preferably, in S2, the remelting depth is 1 to 3 μm.

[0020] Preferably, in S2, the thickness of the prepared ceramic thermal insulation layer is 100-350 μm.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The method disclosed in the present invention for improving the oxidation resistance of the metal bonding layer of the thermal barrier coating is to first prepare the bonding layer on the surface of the high-temperature alloy substrate, then use a pulsed laser to treat the bonding layer so that the splashing particles on the surface of the bonding layer can be remelted, solving the problem of poor contact between the splashing particles and the bonding layer substrate, and finally preparing a ceramic thermal insulation layer on its surface, thereby achieving the purpose of forming a single uniform α-Al2O3 on the surface of the bonding layer during the subsequent service process, effectively improving the oxidation resistance of the bonding layer and the service life of the thermal barrier coating. Through experimental verification, two types of samples (bonding layers after laser treatment and bonding layers not treated by laser) were subjected to 200 hours of oxidation weight gain experiments at 1100°C and atmospheric environment. Compared with the bonding layer not treated by laser, the oxidation resistance of the bonding layer after laser treatment is improved by more than 40%. Compared with the prior art, the scheme of the present invention can directly use commercial powder, is simple to operate without re-plating Al film, has relatively low cost, and has strong on-site operability.

[0023] Furthermore, in order to prevent the vertical reflection of the laser from damaging the laser lens, the horizontal angle between the laser and the sample is set to 45°-60°.

[0024] Furthermore, in order to ensure that all spatter particles on the surface of the bonding layer can be remelted, the selected laser frequency is 100-200K, the scanning speed is 5-15mm / s, and the laser scan is performed three times. The normal direction of the sample surface is used as the axis, and the axis is rotated 120° each time. The purpose is to completely remelt the spatter particles on the surface of the sample into the bonding layer matrix as much as possible.

[0025] Furthermore, in order to avoid secondary oxidation during the laser treatment, argon gas protection needs to be implemented during the laser treatment to reduce or eliminate the secondary oxidation problem caused by the laser treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is the process flow chart of the present invention

[0027] Figure 2The SEM images of the bonding surface before and after laser treatment; (a) is a picture of the bonding layer surface without laser treatment, with more spatter particles on the surface; (b) is a picture of the bonding layer surface after laser treatment, with the spatter particles on the surface remelted;

[0028] Figure 3 Figure 2 is the SEM image of the cross section of the bonding layer after pre-oxidation treatment before and after laser treatment; (a) is the cross section of the bonding layer after direct oxidation without laser treatment, the oxidation condition is serious, and obvious complex oxides are generated; (b) is the cross section of the bonding layer after laser treatment and then oxidation, the oxidation condition is better, and no obvious complex oxides are found. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0030] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0032] See also Figure 1 The preparation process of the present invention comprises:

[0033] First, a nickel-based or cobalt-based metal bonding layer with a thickness of 80-150 μm is prepared on the surface of the high-temperature alloy substrate by thermal spraying technology;

[0034] Then, a pulse laser is used to perform laser scanning on the bonding layer surface to remelt the spatter particles on the bonding layer surface and eliminate the weak bonding between the spatter particles and the bonding layer surface;

[0035] Finally, a ceramic thermal insulation layer with a thickness of 100-350 um is prepared on the surface of the specimen by using one of atmospheric plasma spraying technology, plasma spray-physical vapor deposition technology or electron beam physical vapor deposition technology;

[0036] Example 1

[0037] A nickel-based high-temperature alloy IN718 with a diameter of 25.4 mm and a thickness of 2.5 mm was selected as the high-temperature alloy substrate. Sandblasting was performed on the substrate surface to improve the surface roughness and the bonding force between the bonding layer and the substrate. A NiCoCrAlY metal bonding layer with a thickness of 120 μm was prepared on the surface of the high-temperature alloy substrate using low-pressure plasma spraying technology. The technical parameters of low-pressure plasma spraying are as follows: working pressure of 5000Pa-8000Pa, spraying power of 40KW, argon flow rate of 40SLPM, hydrogen flow rate of 4.5SLPM, and spraying distance of 250mm.

[0038] The surface of the bonding layer was treated with a pulsed laser with an average power of 100W. The laser frequency was 100K, the scanning speed was 10mm / s, and the scanning was three times with each rotation of 120°. The surface morphology of the bonding layer before and after laser treatment was observed under a scanning electron microscope. The two samples with only the bonding layer were subjected to an oxidation weight gain experiment at 1100℃ and 200 hours of heat preservation. The experimental results showed that the average weight gain rate was: 0.2017g / m for the control group (samples not treated with laser) and 0.2017g / m for the control group (samples not treated with laser). 2 h, experimental group (samples remelted after laser surface treatment) is 0.1105g / m 2 h, antioxidant performance increased by 45%.

[0039] Finally, an 8YSZ ceramic thermal insulation layer with a thickness of 250 μm was prepared on the remaining specimen surface by atmospheric plasma spraying. The parameters of atmospheric plasma spraying are as follows: spraying power 42KW, argon flow rate 60SLPM, hydrogen flow rate 4SLPM, powder feeding gas flow rate 7.5SLPM, and spraying distance 80mm.

[0040] Example 2

[0041] A nickel-based high-temperature alloy IN718 with a diameter of 25.4 mm and a thickness of 2.5 mm was selected as the high-temperature alloy substrate. Sandblasting was performed on the substrate surface to improve the surface roughness and the bonding force between the bonding layer and the substrate. A CoNiCrAlY metal bonding layer with a thickness of 150 μm was prepared on the surface of the high-temperature alloy by supersonic flame spraying. The technical parameters of supersonic flame spraying are as follows: oxygen flow rate 1950 SCFH, kerosene flow rate 6 GPH, spraying distance 380 mm, and powder feeder speed 5 RPM.

[0042] The surface of the bonding layer was treated with a pulsed laser with an average power of 80W. The laser frequency was 150K, the scanning speed was 10mm / s, and the scanning was three times with each rotation of 120°. The surface morphology of the bonding layer before and after laser treatment was observed under a scanning electron microscope. The oxidation weight gain experiment was conducted on two samples with only bonding layers at 1100℃ and 200 hours of heat preservation. The experimental results showed that the average weight gain rate was: 0.1986g / m for the control group (samples not treated with laser) and 0.1986g / m for the control group (samples not treated with laser). 2 h, experimental group (sample remelted after laser surface treatment) is 0.0978g / m 2 h, antioxidant performance increased by 50%.

[0043] Finally, an 8YSZ ceramic thermal insulation layer with a thickness of about 250 μm was prepared on the remaining sample surface using atmospheric plasma spraying technology. The specific spraying parameters are as follows: spraying power 42KW, argon flow rate 60SLPM, hydrogen flow rate 4SLPM, powder feeding gas flow rate 7.5SLPM, and spraying distance 80mm.

[0044] according to Figure 2 It can be seen that the bonding layer prepared by supersonic flame spraying has more spatter particles on the surface of the bonding layer that has not been treated with laser, while the spatter particles on the surface of the bonding layer after laser treatment are remelted. Figure 3 The figure shows the cross-sectional images of the bonding layer after heat treatment. (a) is a cross-sectional image of the bonding layer after heat treatment without laser treatment. It can be seen that complex oxides are generated. (b) is a cross-sectional image of the bonding layer after laser treatment and then heat treatment. No obvious complex oxides are found.

[0045] Example 3

[0046] A nickel-based high-temperature alloy IN718 with a diameter of 25.4 mm and a thickness of 2.5 mm was selected as the high-temperature alloy substrate. Sandblasting was performed on the substrate surface to improve the surface roughness and the bonding force between the bonding layer and the substrate. A NiCoCrAlY metal bonding layer with a thickness of 120 μm was prepared on the surface of the high-temperature alloy substrate using low-pressure plasma spraying technology. The technical parameters of low-pressure plasma spraying are as follows: spraying power 40KW, argon flow rate 40SLPM, hydrogen flow rate 4.5SLPM, and spraying distance 250mm.

[0047] The surface of the bonding layer was treated with a pulsed laser with an average power of 100W. The laser frequency was 150K, the scanning speed was 10mm / s, and the scanning was three times with each rotation of 120°. The surface morphology of the bonding layer before and after laser treatment was observed under a scanning electron microscope. The two samples with only bonding layers were subjected to an oxidation weight gain experiment at 1100℃ and 200 hours of heat preservation. The experimental results showed that the average weight gain rate was: 0.2234g / m for the control group (samples not treated with laser) 2 h, experimental group (samples remelted after laser surface treatment) is 0.1026g / m 2 h, antioxidant performance increased by 54%.

[0048] Finally, an 8YSZ ceramic thermal insulation layer with a thickness of about 250 μm was prepared on the remaining sample surface using atmospheric plasma spraying technology. The specific spraying parameters are as follows: spraying power 42KW, argon flow rate 60SLPM, hydrogen flow rate 4SLPM, powder feeding gas flow rate 7.5SLPM, and spraying distance 80mm.

[0049] Example 4

[0050] A nickel-based high-temperature alloy IN718 with a diameter of 25.4 mm and a thickness of 2.5 mm was selected as the high-temperature alloy substrate. Sandblasting was performed on the substrate surface to improve the surface roughness and the bonding force between the bonding layer and the substrate. A CoNiCrAlY metal bonding layer with a thickness of 150 μm was prepared on the surface of the high-temperature alloy by supersonic flame spraying. The technical parameters of supersonic flame spraying are as follows: oxygen flow rate 1950 SCFH, kerosene flow rate 6 GPH, spraying distance 380 mm, and powder feeder speed 5 RPM.

[0051] The surface of the bonding layer was treated with a pulsed laser with an average power of 80W. The laser frequency was 100K, the scanning speed was 10mm / s, and the scanning was three times with each rotation of 120°. The surface morphology of the bonding layer before and after laser treatment was observed under a scanning electron microscope. The two samples with only bonding layers were subjected to an oxidation weight gain experiment at 1100℃ and 200 hours of heat preservation. The experimental results showed that the average weight gain rate was: 0.2021g / m for the control group (samples not treated with laser) 2 h, experimental group (samples remelted after laser surface treatment) is 0.1006g / m 2 h, antioxidant performance increased by 50%.

[0052] Finally, an 8YSZ ceramic thermal insulation layer with a thickness of about 250um was prepared on the remaining sample surface using atmospheric plasma spraying technology. The specific spraying parameters are as follows: spraying power 42KW, argon flow 60SLPM, hydrogen flow 4SLPM, powder feeding gas flow 7.5SLPM, and spraying distance 80mm.

[0053] In summary, based on the characteristics of pulsed laser, which has short single pulse duration, low average power and high peak power, the present invention uses pulsed laser to process the bonding layer surface to effectively remelt the spatter particles into the bonding layer matrix, and can ensure that the surface roughness of the bonding layer does not change significantly. Therefore, the scheme of the present invention uses pulsed laser to process the bonding layer surface to remelt the spatter particles, solves the problem of weak bonding between the spatter particles and the bonding layer matrix, thereby forming a single uniform α-Al2O3 on the bonding layer surface during the subsequent service process, and improving the anti-oxidation performance of the bonding layer and the service life of the thermal barrier coating.

[0054] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for improving the oxidation resistance of a metal bonding layer of a thermal barrier coating, characterized in that: The following steps are involved: S1: preparing a nickel-based or cobalt-based metal bonding layer on the surface of a nickel-based high-temperature alloy substrate by thermal spraying; S2: Perform laser scanning on the bonding layer surface, remelt the splash particles on the bonding layer surface, and eliminate the weak bond between the splash particles and the bonding layer surface; use a pulsed laser for laser scanning, the laser power is between 50W and 200W, the peak power is greater than 10 kW, and the pulse width is less than 10 μs; the laser frequency is 100-200k, the scanning speed is 5-15mm / s, and the laser scans three times, with the normal direction of the sample surface as the axis, and rotate 120° along the axis each time; the remelting depth is 1~3 μm; S3: preparing a ceramic thermal insulation layer on the surface of the specimen treated in S2.

2. The method for improving the oxidation resistance of the metal bonding layer of a thermal barrier coating according to claim 1, characterized in that: In S1, the thermal spraying method used to prepare the nickel-based or cobalt-based metal bonding layer is a low-pressure plasma spraying method or a supersonic flame spraying method.

3. The method for improving the oxidation resistance of the metal bonding layer of a thermal barrier coating according to claim 1, characterized in that: In S1, the powder component elements of the prepared nickel-based or cobalt-based metal bonding layer include Co, Cr, Ni, Al and Y.

4. The method for improving the oxidation resistance of the metal bonding layer of a thermal barrier coating according to claim 1, characterized in that: In S1, the thickness of the prepared nickel-based or cobalt-based metal bonding layer is 80-150 μm.

5. The method for improving the oxidation resistance of the metal bonding layer of a thermal barrier coating according to claim 1, characterized in that: The horizontal angle between the laser and the sample was set to 45°~60°.

6. The method for improving the oxidation resistance of the metal bonding layer of a thermal barrier coating according to claim 1, characterized in that: In S2, an argon atmosphere is used for protection during the laser scanning process.

7. The method for improving the oxidation resistance of the metal bonding layer of a thermal barrier coating according to claim 1, characterized in that: In S2, the thickness of the prepared ceramic thermal insulation layer is 100-350 μm.

Citation Information

Patent Citations

  • Laser micro-texture modified thermal barrier coating for delaying interface TGO growth and preparation process of laser micro-texture modified thermal barrier coating

    CN114807822A